Tracıng And Measurıng Errors In The Roentgenographıc Cephalometry - Abdulvahit Erdem; İsmail Ceylan; Erdal Deniz (Galenos Yayinevi, 1989)
In the present study, thirty cephalometric films which had been used in three different investigations using almost the same parameters were selected and devided into two groups. Twenty-three parameters in the first group and nine parameters in the second, which were used in two and three investigations respectively, were statistically compared. Paired t test was used in the first group and variance analysis in the second group. In conclusion, a lot of parameters exhibited statistically significant variability, while some of them were not.